As relações internacionais entre os estados e a livre concorrência no mercado mundial - Morbidelli, Sidney (2009)
The theme of this thesis involves the analysis of international commerce since its creation and its commercial relationship in the worldwide market, after the emergence of a new universal order promoted by nations that are integrated in economic blocks. The globalization generated the interdependence among countries, forcing them to promote strategies and politics of economic development to assure the attractiveness of external investments and to extend the participation of their territories in worldwide markets. The Anti-Trust and Anti-Dumping rules that in the beginning were scattered and applied only to the internal affairs of the states, started to be systematized also in the universal scenery along the formation of GATT and OMC. With the action of this organization, there was a significant increase of protective measures to the international market pertaining to free competition in search of preservation and the access to the worldwide market. Nevertheless, the OMC have not been able to halt the trust and dumping practice regularly perpetrated by the countries. Its measures are insufficient to prevent satisfactorily in the acts of restriction to free competition and domination in the global market. In 1993, an International Anti-Trust code was created aiming to offer juridical security to the economic agents and their commercial relationship, to assure the free access to the market. The code s objective was to supplement the GATT deficiency in the absence of a universal legislation to competition regarding the question of industrial estate in the extraterritorial space in the states. The legislation was not approved, but the initiative represented a milestone in the harmonization and uniformity of the international right to competition and the legislation was embraced worldwide. Considering this perspective, the current thesis goal is to point out the need for a new international legislation of competition in order to halt the restrictive practices of commerce and the effects of concentration of markets arising with the new global economic order. Thus, it is proposed, the creation by OMC, of an anti-trust international code patterned after the code used by the European Union, which established a centralized authority to defend competition from the limiting present time practices. The code will be binding, defining universal standards and requiring mandatory enforcement by the signatory states of OMC. For the enforcement of the international rules of competition, it is suggested the formation of an international tribunal, again, patterned after the European community. Such tribunal was structured as a supranational organization, whose juridical laws are legally binding and applicable to all member countries, through the primacy of community laws concerning national rights. The international tribunal of competition will be directed by the OMC, which is the indicated forum to the treatment of worldwide competition and it will oversee the application and execution of the tribunal rules of the anti-trust international code